Local causes of essential medicines shortages from the perspective of supply chain professionals in Saudi Arabia - Yazed AlRuthia; Nouf Mohammed Almutiri; Raghdah Musa Almutairi; Omar Almohammed; Hani Alhamdan; Sobhi Ali El-Haddad; Yousif Abdu Asiri (Elsevier, 2023)
Background: The global supply chains of essential medicines faced frequent disruptions over the past five years, particularly during the COVID-19 pandemic. Different causes of prescription drug supply interruptions have been identified in Saudi Arabia. However, studies have yet to explore the views of pharmaceutical supply chain personnel regarding the causes of these interruptions. Therefore, this study aimed to survey individuals working in the pharmaceutical supply chains about their views on the observed interruptions in the supply of some essential drugs. Methods: This was a questionnaire-based cross-sectional study. The 10-item questionnaire was created based on the findings of previously published research that investigated the root causes of essential drug shortages and the impact of COVID-19 pandemic on the supply chains of essential drugs in Saudi Arabia. Purposive sampling was used to identify individuals with at least one year of experience in the area of the pharmaceutical supply chain, and the data collection occurred between April 19th, 2022 and October 23rd, 2022. In addition, descriptive statistics (e.g., frequencies and percentages) were conducted to present the views of the respondents. Results: Seventy-nine pharmaceutical supply chain specialists accepted the invitation and completed the questionnaire. About two-thirds (69.62%) of the respondents reported that centralized pharmaceutical procurement negatively affected the supply chain of essential drugs. Procurement of unregistered medications by the Saudi Food and Drug Authority (SFDA), as well as generic drugs with a history of recalls, and failure to supply requested quantities were the three most commonly reported reasons behind the observed interruptions in the supply of some essential drugs according to those respondents with a negative view of the centralized procurement. Furthermore, failure of pharmaceutical companies to inform SFDA of potential drug shortages, manufacturing issues, poor demand forecasting, unpredictable increase in demand, and low prices of essential drugs were also believed to be behind the observed interruptions in the supply of some essential medicines. Conclusion: The majority of surveyed pharmaceutical supply chain professionals held negative views about the role of centralized pharmaceutical procurement in exacerbating the issues with essential medicines supply chain. Future research should examine different strategies to improve purchasing and procurement practices in Saudi Arabia.